Analysis of the factors affecting employee productivity at the Regional Planning and Development Agency of Mimika Regency - Ayamiseba, Daud Erwin; Hutajulu, Halomoan; Marlissa, Elsyan R. (Goodwood Publishing, 2025)
Purpose: This study aims to examine the determinants of employee productivity at the Regional Planning and Development Agency (Bappeda) in Mimika Regency. Specifically, it investigates (1) the relationship between salary and employee productivity, (2) the relationship between work relationships and employee productivity, (3) the effect of the work environment on productivity, and (4) the impact of promotion on productivity. Research Methodology: A quantitative method using SEM-PLS correlational analysis was applied. Data were obtained via a Likert-scale questionnaire. The study conducted validity, reliability, and hypothesis testing to assess relationship strength and significance among variables, ensuring robust measurement and accurate evaluation of the proposed research model. Results: The study found salary (X?) negatively influenced productivity, indicating the need to reassess compensation. Work relationships (X?) and environment (X?) positively affected productivity, highlighting collaboration and supportive conditions. Promotion (X?) showed no significant effect, suggesting weaknesses in promotion mechanisms requiring attention to improve organizational motivation and employee outcome. Conclusions: Employee productivity is more strongly influenced by relational and environmental factors than salary and promotion. Therefore, organizational improvements should focus on fostering positive relationships and enhancing the physical and psychological work environments. Limitations: This study was limited to a single regional agency, which may have affected the generalizability of the findings. Additionally, the cross-sectional design does not capture the long-term dynamics. Contribution: This study contributes to the public sector human resource management literature by highlighting the relative importance of workplace relationships and conditions over financial and promotional factors in improving employee productivity.